Hands on action-research in construction of the teaching profession: a scientific contribution in the initial teacher training of the University of Madeira (UMa) - Gouveia, M. F. B. Pestana (2020)
Action research is more than just a method of searching scientific knowledge in the field of Educational Sciences. It brings together multiple dimensions of educational practice which involves action, observation and contextualized and systematic reflection leading to curricular and organizational development, along with the construction of the teaching profession. Action research aims to find solutions to emerging problems through the creation of curricular strategies that promote pedagogical innovation and improve learning. The Master's degree in Preschool Education and Primary Education at the University of Madeira is based on these assumptions and has a curricular unit named Action Research Project which is implemented in real contexts of Pedagogical Practice in schools. This paper is intended to report the beginning of this reflexive process in an attempt to broaden the discussion of teacher training to new audiences. It is important to examine experiences of the use of action research, starting from the diagnosis of problems, passing through the collection and analysis of data as well as the systematization of processes and knowledge and culminating in the realization of scientific reports.